Applying Structural Systems Thinking to Frame Perspectives on Social Work Innovation. (March 2017) - Stringfellow, Erin J.
Objective: Innovation will be key to the success of the Grand Challenges Initiative in social work. A structural systems framework based in system dynamics could be useful for considering how to advance innovation. Method: Diagrams using system dynamics conventions were developed to link common themes across concept papers written by social work faculty members and graduate students ( N = 19). Results: Transdisciplinary teams and ethical partnerships with communities and practitioners will be needed to responsibly develop high-quality innovative solutions. A useful next step would be to clarify to what extent factors that could "make or break" these partnerships arise from within versus outside of the field of social work and how this has changed over time. Conclusions: Advancing innovation in social work will mean making decisions in a complex, ever-changing system. Principles and tools from methods that account for complexity, such as system dynamics, can help improve this decision-making process.